Delegating an Employer’s Managerial Prerogative to Artificial Intelligence: A Challenge of The Present or a Projection of The Future? (Ius Novum, 2026)
The use of artificial intelligence (AI) in employment is now a fact. In this article, the author examines whether it is possible for AI to exercise managerial authority over employees. The discussion of the substantive elements of this issue is preceded by an analysis of whether managerial prerogative can only lawfully be exercised by natural persons or whether it can be lawfully exercised by artificial intelligence. If the findings of this analysis indicate that AI can exercise managerial prerogative, this provides the starting point for addressing the substantive issues concerned. The analysis is conducted on multiple levels: on the one hand, it examines the requirements that interpersonal communication must satisfy; on the other hand, it analyses the current stage of AI’s technological advancement. The author recognises that a workforce cannot be managed effectively without accounting for emotional elements as a determining factor in human activity, which may be of particular relevance to the effective implementation of instructions received by employees. Recognition of the importance of emotions means that the extent to which AI is capable, at the current stage of technological development, of using emotions to achieve its intended goals, must be considered, and whether one can at all speak of emotional intelligence with regard to AI. The author examines Emotional Artificial Intelligence technology, which is undergoing evolutionary development. These reflections determine to what extent EAI currently enables the managerial prerogative described in the title to be exercised over employees, while simultaneously considering the advantages and risks associated with the extensive use of artificial intelligence in the analysed aspect of employment relations.
Keywords: artificial intelligence, emotional intelligence, managerial prerogative, emotions, subordination